THE EFFECT OF GENDER AND INCOME ON CONSUMER STYLES / Cinsiyet Ve Gelirin Tüketici Tarzına Etkisi - Lale Babuş; Gülçin Bilgin Turna (Uluslararası Ekonomi, İşletme ve Politika Dergisi, 2020)
The aim of this study is to determine the effect of gender and income on consumer styles. The questionnaire was conducted with Recep Tayyip Erdogan University students (n=346) in Rize/Turkey. Hypotheses were tested by Mann Whitney U Test, Kruskal Wallis Test and Spearman Correlation Analysis along with Exploratory Factor Analysis. Most of the participants are price-oriented students who exhibit a perfectionist consumer style. While women are more likely to be confused and have instant buying tendency, men avoid shopping. As income level increases, price sensitivity decreases whereas instant buying and perfectionism increase. Perfectionist consumers are also focused on brand and fashion. Price sensitive people usually buy by comparing. Instant buyers are not price sensitive. Those who experience information confusion due to the excess of alternatives tend to buy habitually.